2015
DOI: 10.1016/j.nucmedbio.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Dose-specific transcriptional responses in thyroid tissue in mice after 131I administration

Abstract: This work may contribute with new knowledge of potential normal tissue effects or complications that may occur after exposure to ionizing radiation in diagnostic and therapeutic nuclear medicine, and due to radioactive fallout or accident with radionuclide spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 30 publications
6
22
1
Order By: Relevance
“…Few GO terms related to DNA and gene expression integrity were identified in the present study. This is in agreement with previous results on transcriptional changes in thyroid tissue after 131 I and 211 At [ 11 , 13 ]. Monte Carlo simulations have shown that 1.2 Gy after 211 At irradiation corresponds to a mean value of one alpha particle track per thyroid follicular cell [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Few GO terms related to DNA and gene expression integrity were identified in the present study. This is in agreement with previous results on transcriptional changes in thyroid tissue after 131 I and 211 At [ 11 , 13 ]. Monte Carlo simulations have shown that 1.2 Gy after 211 At irradiation corresponds to a mean value of one alpha particle track per thyroid follicular cell [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…Few of the 102 previously proposed genes were identified in the present study. This is in agreement with our previous studies on thyroid tissue after 131 I and 211 At administration and in kidneys after 177 Lu-octreotate administration [ 11 , 13 , 16 ]. An explanation may be that most of these biomarkers were defined in in vitro studies and after acute external exposure.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…At high doses (0.5, 4 Gy), the latter activated P53 pathway while the former triggered TGFβ. In accordance to that, TGFβ and SMAD (canonical TGFβ pathway) were also regulated in normal thyroid gland after 131 I administration in mice 23 and the profound diversity of biological responses to radiation doses were also recapitulated in vivo. So far, the main limitations of these models are: 1) the lack of temporal points; 2) most of the approaches have been conducted in immortalized cells; 3) Speciesspecific molecular alterations in response to radiation (i.e, RET/PTC only detected in humans).…”
Section: Acute Effects Of Ionization Radiation On Thyroid Cellssupporting
confidence: 76%
“…To the best of our knowledge, this study is the first to carry out RNA sequencing to obtain the gene expression profile of human thyrocytes following 131 I exposure. Thyroid transcriptomic data after 131 I exposure have been obtained by microarray analysis in rat and mouse models and showed a distinct dose-dependent gene response (53,54). Given the limited number of conditions that can be examined in a single primary culture, one limitation of this study is the relatively small number of samples that at our disposal (4 samples for each condition) for RNA sequencing.…”
Section: And γ Radiation Did Not Induce Apoptosis In Human Thyrocytmentioning
confidence: 99%